UJI SARI DAUN JAMBU BIJI (Psidium guajava L.) TERHADAP PERTUMBUHAN BAKTERI Escherechia coli - Nolia, Winda Defri (STKIP PGRI Sumbar, 2014)
Escherechia coli is part of the normal microbiota of the intestinal tract , E. coli however many years regarded as a cause of diarrhea in humans and animals . One of the commonly used medicinal plants as an antidiarrheal community is guava leaves ( Psidium guajava L. ) . Guava leaves contain various phytochemical components that can be used as an antidiarrheal . Antidiarrheal compounds in the leaves of guava include essential oils , tannins and flavonoids . The purpose of this study was to determine the ability of guava leaf extract with and without heating heated in inhibiting the growth of E. coli bacteria . This study was conducted in May 2014 at the Laboratory of Basic Biology Education STKIP PGRI West Sumatra . Using a completely randomized design consisting of seven treatments and three replications . Data were analyzed by ANOVA and further test DNMRT at level Î± of 5% . The results showed that the extract of guava leaves with heating and without heating can inhibit the growth of E. coli bacteria.